2014
DOI: 10.1155/2014/293925
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotides Regulate Secretion of the Inflammatory Chemokine CCL2 from Human Macrophages and Monocytes

Abstract: CCL2 is an important inflammatory chemokine involved in monocyte recruitment to inflamed tissues. The extracellular nucleotide signalling molecules UTP and ATP acting via the P2Y2 receptor are known to induce CCL2 secretion in macrophages. We confirmed this in the human THP-1 monocytic cell line showing that UTP is as efficient as LPS at inducing CCL2 at early time points (2–6 hours). Expression and calcium mobilisation experiments confirmed the presence of functional P2Y2 receptors on THP-1 cells. UTP stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
0
16
0
2
Order By: Relevance
“…In the presence of eATP alone, concentrations from 1 to 100 nM in the absence of chemokine increased primary monocyte migration by approximately 10 % (see supplementary data). This low level of activity is likely the result CCL2 secreted by monocytes in response to eATP [37]. In the presence of CCL2, Apyrase blocked migration of the control primary monocytes by 50 %, indicating endogenous production and release of eATP occurred in the Transwell assay, possibly by CCL2 activation of eATP release from migrating monocytes or as a result of eATP release from dying cells in the freshly isolated PBMC preparation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the presence of eATP alone, concentrations from 1 to 100 nM in the absence of chemokine increased primary monocyte migration by approximately 10 % (see supplementary data). This low level of activity is likely the result CCL2 secreted by monocytes in response to eATP [37]. In the presence of CCL2, Apyrase blocked migration of the control primary monocytes by 50 %, indicating endogenous production and release of eATP occurred in the Transwell assay, possibly by CCL2 activation of eATP release from migrating monocytes or as a result of eATP release from dying cells in the freshly isolated PBMC preparation.…”
Section: Discussionmentioning
confidence: 98%
“…For example, the P2Y2 receptor was identified as the nucleotide receptor for eATP and eUTP which induced CCL2 secretion from CD14+ monocytes and the THP-1 myeloid cell line. These researchers found that the selective antagonist, suramin, did not block receptor activity reproducibly at the higher concentrations of nucleotides often used for in vitro studies [37]. By contrast, Pam 3 CSK 4 -induced chemokine production by human monocytes was reported to be dependent on synergism between TLR2 and nucleotides, as the addition of Apyrase abrogated the response.…”
Section: Discussionmentioning
confidence: 99%
“…Mice null for P2RY2 showed a decreased ability to recruit monocytes and macrophages upon activation of nucleotides from apoptotic cells . P2RY2 is also known to induce CCL2 secretion in macrophages, and coding variants in the receptor have been shown to influence secretion of this proinflammatory chemokine .…”
Section: Discussionmentioning
confidence: 99%
“…Also, other molecules, such as TLR4, have to be taken under consideration as HA receptors [36]. Moreover, lipids, heat shock proteins [37] or nucleotides [38] carried by TMVs may be involved in the induction of chemokines. Other components of TMVs may address the question about the role of CD44H in the signalling pathway for the chemokines which secretion was unaffected by anti-CD44 mAb and TMVs (CXCL8, CCL2 and CCL3).…”
Section: Discussionmentioning
confidence: 99%